“It’s Brought Me a Lot Closer to Who I Am”: A Mixed Methods Study of Posttraumatic Growth and Positive Change Following a First Episode of Psychosis - Jordan, Gerald; Malla, Ashok; Iyer, Srividya N. (Frontiers in Psychiatry, 2019)
Background: A first episode of psychosis is often a traumatic experience that may also lead to positive change, a phenomenon that has received little attention. This knowledge gap may impede service providers’ capacity to foster positive change among service users. Objective: To investigate aspects of positive change among persons receiving early intervention services for psychosis. Design: The study objective was addressed using a mixed methods convergent design, which entailed simultaneously employing qualitative and quantitative methods. Setting: This study was conducted at a specialized early intervention service for psychosis based in Montreal, Quebec, Canada. Participants: Participants included service users receiving services at an early intervention service for psychosis. Participants had to be fluent in English or French, be clinically stable enough to take part in the study, and have received at least 6 months of treatment. Participants were conveniently sampled in the quantitative component and purposefully sampled in the qualitative component. The quantitative component was carried out using a cross-sectional survey design. Ninety-four participants completed the Posttraumatic Growth Inventory, a widely used measure of positive change. Data on the extent and domains of posttraumatic growth were summarized using descriptive statistics. The qualitative component was carried out using a qualitative descriptive approach. Semistructured interviews were conducted with 12 participants. Data were analyzed using thematic analysis. Findings from both components were integrated using a weaving method in the discussion section. Results: Quantitative results indicated that most participants reported a moderate amounts of posttraumatic growth. A greater appreciation of life was the most commonly endorsed domain, whereas spiritual growth was the least commonly endorsed domain. The qualitative results revealed that in addition to suffering, participants experienced positive changes, such as improved health and personality, and a stronger sense of self; stronger, more balanced religiosity and spirituality; improved relationships with others; and improved lifestyles, goals, and expectations for the future. Conclusions: Positive change may be a common phenomenon in the aftermath of first episode psychosis. The study findings may provide hope to those who have experienced a first episode of psychosis and can inform efforts by early intervention services to provide recovery-oriented, growth-focused care.